Acute CNS demyelination in a subject with cerebellar ataxia following the first dose of COVID-19 vaccine; a case report - Omid Mirmosayyeb; Sara Bagherieh; Vahid Shaygannejad (Taylor & Francis Group, 2021)
Vaccination-induced demyelination is a rare, unusual side effect of certain vaccines which can cause significant damage to patient's sensory-motor abilities within days. Although COVID-19 vaccines go through rigorous clinical trials before they are injected to the general population, certain unexpected side effects remain inevitable. We herein describe a case of a 42-year-old woman who experienced acute demyelination 10 days after the Oxford-AstraZeneca vaccination. To the best of our knowledge, this is the first case of such nature and severity described regarding COVID-19 vaccines' side effects.